2015
DOI: 10.1007/s11239-015-1262-y
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of preadmission oral anticoagulation with vitamin K antagonists and ischemic stroke severity and outcome in patients with atrial fibrillation

Abstract: It is unclear whether vitamin K antagonists affect stroke severity and outcome in patients with atrial fibrillation (AF). We aimed to evaluate this association. We prospectively studied 539 consecutive patients admitted with acute ischemic stroke (41.2 % males, age 78.9 ± 6.6 years). The severity of stroke was assessed at admission with the National Institutes of Health Stroke Scale (NIHSS). The outcome was assessed with dependency rates at discharge (modified Rankin scale 2-5) and with in-hospital mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In real world clinical practice, the economic costs should also be accounted for. 18 In previous studies, therapeutic warfarin was associated with reduced severity of IS at presentation and reduced disability or death at discharge in patients with AF, 19 , 20 which is consistent with the current study. We also found that the direct costs for patients with IS who had undergone warfarin treatment before admission were less than those for patients who did not undergo warfarin treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In real world clinical practice, the economic costs should also be accounted for. 18 In previous studies, therapeutic warfarin was associated with reduced severity of IS at presentation and reduced disability or death at discharge in patients with AF, 19 , 20 which is consistent with the current study. We also found that the direct costs for patients with IS who had undergone warfarin treatment before admission were less than those for patients who did not undergo warfarin treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, AF patients reap additional benefits from OACs, apart from ischemic stroke risk reduction. AF patients on warfarin with an INR ≥ 2 immediately before stroke have smaller brain infarcts 24,25 and lower stroke severity, 24 recurrence, 26 disability, 16,24,2729 and mortality 16,27,29,30 relative to patients only taking antiplatelet agents, no antithrombotic drugs, or warfarin with an INR < 2.…”
Section: Benefits Of Oral Anticoagulants For Af Patientsmentioning
confidence: 99%
“…It is well established that single antiplatelet treatment has limited efficacy in reducing cardiovascular events in patients with AF compared with placebo [23,24] and therefore, it is recommended only in patients with AF who have contraindications to oral anticoagulants or who refuse treatment with the latter agents [25] . Moreover, several studies showed that antiplatelet treatment prior to stroke in patients with AF does not affect the severity of stroke or the short-term outcome [26][27][28][29][30] . Therefore, we included in our analyses only patients without AF, prosthetic valve or hemodynamically relevant heart valve disease and we showed that clopidogrel attenuates the severity of non-cardioembolic stroke.…”
Section: Discussionmentioning
confidence: 99%